Investment Science Solutions - Investment Science Chapter 3...

Info icon This preview shows pages 1–6. Sign up to view the full content.

View Full Document Right Arrow Icon
Investment Science Chapter 3 Dr. James A. Tzitzouris <[email protected]> 3.1 Use A = rP 1 - 1 (1+ r ) n with r = 7 / 12 = 0 . 58%, P = $25 , 000, and n = 7 × 12 = 84, to obtain A = $377 . 32. 3.2 Observe that since the net present value of X is P , the cash flow stream arrived at by cycling X is equivalent to one obtained by receiving payment of P every n + 1 periods (since k = 0 , . . . , n ). Let d = 1 / (1 + r ). Then P = P k =0 ( d n +1 ) k . Solving explicitly for the geometric series, we have that P = P 1 - d n +1 . Denoting the annual worth by A , we must have A = rP 1 - d n , so that solving for P as a function of P and substituting the result into the equation for A , we arrive at A = r 1 - d n +1 1 - d n P . 1
Image of page 1

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Investment Science Chapter 4 Solutions to Suggested Problems Dr. James A. Tzitzouris <[email protected]> 4.1 (One forward rate) f 1 , 2 = (1 + s 2 ) 2 (1 + s 1 ) - 1 = 1 . 069 2 1 . 063 - 1 = 7 . 5% 4.2 (Spot Update) Use f 1 ,k = (1 + s k ) k 1 + s 1 1 / ( k - 1) - 1 . Hence, for example, f 1 ,k = (1 . 061) 6 1 . 05 1 / 5 - 1 = 6 . 32% . All values are f 1 , 2 f 1 , 3 f 1 , 4 f 1 , 5 f 1 , 6 5 . 60 5 . 90 6 . 07 6 . 25 6 . 32 1
Image of page 2
4.3 (Construction of a zero) Use a combination of the two bonds: let x be the number of 9% bonds, and y teh number of 7% bonds. Select x and y to satisfy 9 x + 7 y = 0 , x + y = 1 . The first equation makes the net coupon zero. The second makes the face value equal to 100. These equations give x = - 3 . 5, and y = 4 . 5, respectively. The price is P = - 3 . 5 × 101 . 00 + 4 . 5 × 93 . 20 = 65 . 90. 4.5 (Instantaneous rates) (a) e s ( t 2 ) t 2 = e s ( t 1 ) t 1 e f t 1 ,t 2 ( t 2 - t 1 ) = f t 1 ,t 2 = s ( t 2 ) t 2 - s ( t 1 ) t 1 t 2 - t 1 (b) r ( t ) = lim t t 1 s ( t ) t - s ( t 1 ) t 1 t - t 1 = d [ s ( t ) t ] dt = s ( t ) + s ( t ) (c) We have d (ln x ( t )) = r ( t ) dt, = s ( t ) dt + s ( t ) dt, = d [ s ( t ) t ] . Hence, ln x ( t ) = ln x (0) + s ( t ) t, and finally that x ( t ) = x (0) e s ( t ) t . This is in agreement with the invariance property of expectation dynamics. Investing continuously give the same result as investing in a bond that matures at time t . 4.6 (Discount conversion) 2
Image of page 3

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
The discount factors are found by successive multiplication. For example, d 0 , 2 = d 0 , 1 d 1 , 2 = 0 . 950 × 0 . 940 = 0 . 893 . The complete set is 0 . 950, 0 . 893, 0 . 770, 0 . 707, 0 . 646. 4.7 (Bond taxes) Let t be the tax rate, x i be the number of bond i purchased, c i be the coupon of bond i , p i be the price of bond i . To create a zero coupon bond, we require, first, that the after tax coupons match. Hence x 1 (1 - t ) c 1 + x 2 (1 - t ) c 2 = 0 , which reduces to x 1 c 1 + x 2 c 2 = 0 . Next, we require that the after tax final cash flows match. Hence p 0 = x 1 p 1 + x 2 p 2 . Using this last relation in the equationfor final cash flow, we find x 1 + x 2 = 1 . Combining these equations, we find that p 0 = c 2 p 1 - c 1 p 2 c 2 - c 1 . After plugging in the given values, we find that p 0 = 37 . 64 . 4.8 (Real zeros) We assume that with coupon bonds there is a capital gains tax at maturity. We replicate the zero- coupon bond’s after-tax cash flows using bonds 1 and 2. Let x i be the amount of bond i required 3
Image of page 4
(a) d 0 , 1 d 0 , 2 d 0 , 3 d 0 , 4 d 0 , 5 d 0 , 6 0 . 9524 0 . 9018 0 . 8492 0 . 7981 0 . 7472 0 . 7010 = NPV = 9 . 497 (b) Year 0 1 2 34 5 6 Cash Flow - 40 10 10 10 10 10 10 Discount 0 . 9524 0 . 9469 0 . 9416 0 . 9399 0 . 9362 9381 PV( n ) 9 . 497 51 . 970 44 . 324 36 . 453 28 . 144 19 . 381 10 . 000 4.12 (Pure duration) P ( λ ) = n k =0 x k (1 + s k /m ) - k = n k =0 x k (1 + s 0 k /m ) e λ/m - k , dP ( λ ) = n k =0 x k - k m (1 + s 0 k /m ) e λ/m - k - 1 (1 + s 0 k /m ) e λ/m , = n k =0 x k - k m (1 + s k /m ) - k , - 1 P ( λ ) dP ( λ ) = n k =0 x k ( k m ) (1 + s k /m ) - k n k =0 x
Image of page 5

Info icon This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Image of page 6
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

What students are saying

  • Left Quote Icon

    As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

    Student Picture

    Kiran Temple University Fox School of Business ‘17, Course Hero Intern

  • Left Quote Icon

    I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

    Student Picture

    Dana University of Pennsylvania ‘17, Course Hero Intern

  • Left Quote Icon

    The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

    Student Picture

    Jill Tulane University ‘16, Course Hero Intern